Model Pembelajaran Discovery Terbimbing: Apakah dapat Meningkatkan Hasil Belajar Kogitif Fisika Peserta Didik - Ekawati Ekawati; Nurlina Nurlina; Dewi Hikmah Marisda (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2020)
The low learning outcomes of students in the main problem in this study. This research is a pre-experimental research with reference to the One Group Pretest-Posttest Design research design. This study aims to determine whether there is an increase in the cognitive physics learning outcomes of class X MIPA students at SMA Negeri 9 Enrekang after being taught by guided discovery learning model. This research lasted for six weeks with a total sample of 28 students of class X MIPA 2 SMA Negeri 9 Enrekang. The research instrument used was a multiple choice test of physics learning outcomes with cognitive aspects including levels of remembering (C1), understanding (C2), applying (C3), and analyzing (C4). Prior to use, this research instrument has been declared valid and reliable by experts. From the research results, it can be concluded that there is an increase in physics learning outcomes in the cognitive domain of class X MIPA 2 SMA Negeri 9 Enrekang on motion material after being taught by the Guided Discovery learning model, with a gain index of 0.55, in the medium category.